Review of high-speed phase accumulator for direct digital frequency synthesizer - Abdulkareem Dawah Abbas (International Journal of Electrical and Computer Engineering (IJECE), 2020)
A review of high-speed pipelined phase accumulator (PA) is proposed in this paper. The detail explanation of ideas, methods and techniques used in previous researches to improve the PA throughput designs were surveyed. The Brent–Kung (BK) adder was modified in this paper to be applied in pipelined PA architecture. A comparison of different adder circuits, includes a modified BK, ripple carry adder (RCA), Kogge-Stone adder (KS) and other prefix adders were applied to architect the PA based on Pipeline technique. The presented pipelined PA design circuit with multiple frequency control word (FCW) and different adders were coded Verilog hardware description language (HDL) code, compiled and verified with field programmable gate array (FPGA) kit platform. The comparison result shows that the modified BK adder has fast performances. The shifted clocking technique is utilized in the proposed pipelined PA circuit to reduce the unwanted repetitive D-flip flop (DFF) registers (coming from the pipeline technique), while preserving the high speed.